2018
DOI: 10.1186/s12905-017-0502-z
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual health and school absenteeism among adolescent girls in Uganda (MENISCUS): a feasibility study

Abstract: Background: Management of menstruation can present substantial challenges to girls in low-income settings. In preparation for a menstrual hygiene intervention to reduce school absenteeism in Uganda, this study aimed to investigate menstruation management practices, barriers and facilitators, and the influence of menstruation on school absenteeism among secondary school students in a peri-urban district of Uganda. Methods: Qualitative and quantitative studies were conducted among consenting girls and boys aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
206
7
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(237 citation statements)
references
References 27 publications
18
206
7
6
Order By: Relevance
“…Pain was also associated with school absenteeism in our study as has been reported from studies with adolescent girls in Uganda . Although evidence for delivering pain medication and its impact on absenteeism is limited , taboos and myths surrounding the use of pain medication during menstruation have been reported in other contexts and should be considered in the design of interventions to support pain management for menstruating girls in Indonesia. Delivering comprehensive sexual and reproductive health education programmes that address knowledge and practical skills relating to menstruation and MHM, including pain management, may contribute to reducing absenteeism in this context.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Pain was also associated with school absenteeism in our study as has been reported from studies with adolescent girls in Uganda . Although evidence for delivering pain medication and its impact on absenteeism is limited , taboos and myths surrounding the use of pain medication during menstruation have been reported in other contexts and should be considered in the design of interventions to support pain management for menstruating girls in Indonesia. Delivering comprehensive sexual and reproductive health education programmes that address knowledge and practical skills relating to menstruation and MHM, including pain management, may contribute to reducing absenteeism in this context.…”
Section: Discussionmentioning
confidence: 94%
“…Girls in higher grades were more likely to report absenteeism due to menstruation during their last menstrual period. Miiro et al [34]. also found that missing school during a girl's most recent menstruation was associated with older age.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Data emerging from the African context suggest that girls may miss school due to their menses [10][11][12][13]. However, there exist a number of reasons why a learner may miss school while menstruating, including physical symptoms, shame, secrecy and fear of leakage, access to products and/or ability to manage menstruation at school [5,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%